Resistance analysis of grape Botrytis cinerea based on PCR and sequencing technology - Zhang, Hongmei; Jiang, Huimin (Cellular and Molecular Biology, 2022)
Resistance of grape Botrytis cinerea was analyzed based on PCR and sequencing technology, which provided a reasonable basis for guiding the species and usage of grape Botrytis cinerea. 104 monospora strains of grape B. cinerea were collected from the main grape-producing areas of China. After isolation and purification, the grape B. cinerea DNA was extracted, and PCR primers were designed according to the resistance mechanism of pyrimethene to pyrimethamines, pyridamines and diformolines. Sequence analysis showed that the resistance frequency of B. cinerea to pyrimidine was 22.22%-62.5%, the high-resistant strain frequency was 44.23%, and the mid-temperature zone was 62.5%. The total resistance rate of B. cinerea to pyrimidine was 42.60%. The resistance rate of B. cinerea to pyrimidine was 42.60%. Resistance frequencies of grape gray mold strains were significantly different. The resistance frequencies of grape gray mold strains to pyridimide were significant. The highest resistance frequencies of grape gray mold strains were 53.42% in the cool temperature zone. Only 3.85% of grape gray mold strains showed resistance to pyridimide. Therefore, the resistance of Grape B. cinerea to pyrimidine and pyrimidine is relatively common, and the resistance to enoylmorpholine is still in the initial stage.